2021
DOI: 10.1002/ptr.7130
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide downregulates the VEGF/SphK1/S1P pathway and alleviates angiogenesis in rheumatoid arthritis in vivo and in vitro

Abstract: The VEGF/SphK1/S1P pathway is closely related to angiogenesis in rheumatoid arthritis (RA), but the precise underlying mechanisms are unclear at present. Here, we explored the involvement of the VEGF/SphK1/S1P cascade in RA models and determined the effects of GE intervention. Our results showed abnormal expression of proteins related to this pathway in RA synovial tissue. Treatment with GE effectively regulated the signal axis, inhibited angiogenesis, and alleviated RA symptoms. In vitro, TNF‐ɑ enhanced the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Many studies [26][27][28] had confirmed that TGF-β1, VEGF and MMP9 are inevitable in the biological process of angiogenesis. Studies 29,30 had also confirmed that regulated by VEGF, angiopoietin and fibroblast growth factor, endothelial cells can start to proliferate and migrate to the capillary formation, inducing angiogenesis, which is significant for the proper wound healing. Otherwise, MMP9 can be secreted by fibroblasts, macrophages, neutrophils and epithelial cells to degradate collagen and extracellular matrix, thus contributing to angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…Many studies [26][27][28] had confirmed that TGF-β1, VEGF and MMP9 are inevitable in the biological process of angiogenesis. Studies 29,30 had also confirmed that regulated by VEGF, angiopoietin and fibroblast growth factor, endothelial cells can start to proliferate and migrate to the capillary formation, inducing angiogenesis, which is significant for the proper wound healing. Otherwise, MMP9 can be secreted by fibroblasts, macrophages, neutrophils and epithelial cells to degradate collagen and extracellular matrix, thus contributing to angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…2 E). Those shared DEGs identified in IPF-FB samples mainly indicated invasive signatures in fibrotic diseases (GPNMB, TENM3) (Palisoc et al 2022 ; Athwal et al 2018 ; Murakami et al 2010 ), cell focal adhesion (LIMS1) (Sandfort et al 2010 ; Stanchi et al 2009 ), cell cycle (MDGA1) (Lu et al 2008 ), and angiogenesis (SPHK1) (Wang et al 2021 ) (Fig. 2 G, H).…”
Section: Resultsmentioning
confidence: 99%
“…Geniposide has been reported to up-regulate PPARγ in lipopolysaccharide (LPS)-stimulated human renal tubular epithelial (HK-2) cells and cecal ligation in puncture-induced septic mice to improve renal injury in sepsis (Liu et al, 2020). Moreover, VEGF-A was also predicted as a geniposide-related target (Jin et al, 2021), as geniposide reduced the expression of VEGF-A to attenuate angiogenesis in rheumatoid arthritis (Wang et al, 2021). Here, the protein expression of PPARγ was enhanced by geniposide in NSCLC, and antagonist of PPARγ reversed geniposide-induced up-regulation of PPARγ and down-regulation of VEGF-A, suggesting that geniposide reduced VEGF-A in NSCLC through up-regulation of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) with conditioned medium (Invitrogen) were seeded in 24-well plates precoated with basement membrane matrix containing reduced growth factor (Invitrogen) according to a previous study (Wang et al, 2021). The culture medium of A549 and NCI-H1299 cells with indicated incubation and transfection was added into each well, and incubated for 6 h. Cells were then washed and fixed with 4% paraformaldehyde.…”
Section: Tube Formation Assaymentioning
confidence: 99%